Pengaruh Goal Setting terhadap Prokrastinasi Akademik Mahasiswa yang Mengikuti Organisasi: The Influence of Goal Setting on Academic Procrastination of Students Who Join Organizations - M. Nor Faizi; Muhammad Arsyad; Ririanti Rachmayanie Jamain (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Students in higher education often face dual academic and non-academic demands, which require the ability to manage time, energy, and responsibilities in a balanced manner. The inability to set priorities often triggers academic procrastination, namely the tendency to delay completing college assignments, which results in decreased academic achievement. Therefore, students need to have a clear scale of priorities to balance college activities with organisational involvement or other additional activities. One concrete form of this priority scale is goal setting, which plays a role in helping students formulate goals, manage responsibilities, and minimise academic procrastination behaviour. This study aims to analyse the effect of goal setting on the academic procrastination of students who participate in organisations. The method used in this study is quantitative with a type of influence research. The sample consisted of 280 students involved in organisations and was selected through a simple random sampling technique. Data were analysed using simple linear regression. Based on the simple regression analysis results, it can be concluded that the alternative hypothesis (Ha) is accepted. This indicates that goal setting (X) affects academic procrastination (Y) in students who participate in organisations. This is supported by the F-count value of 222.019 with a significance level of 0.001, which means it is less than 0.05. Therefore, it can be concluded that goal setting (X) influences academic procrastination (Y).